Nonfarm Microenterprise Performance and the Investment Climate : Evidence from Rural Ethiopia - Loening, Josef; Rijkers, Bob; Söderbom, Måns (World Bank, Washington, DC, 2012)
This paper uses uniquely matched household, enterprise and community survey data from four major regions in rural Ethiopia to characterize the performance, constraints and opportunities of nonfarm enterprises. The nonfarm enterprise sector is sizeable, particularly important for women, and plays an important role during the low season for agriculture, when alternative job opportunities are limited. Returns to nonfarm enterprise employment are low on average and especially so for female-headed enterprises. Women nevertheless have much higher participation rates than men, which attest to their marginalized position in the labor market. Most enterprises are very small and rely almost exclusively on household members to provide the required labor inputs. Few firms add to their capital stock or increase their labor inputs after startup. Local fluctuations in predicted crop performance affect the performance of nonfarm enterprises, because of the predominant role played by the agricultural sector. Enterprise performance is also affected by the localized nature of sales and limited market integration for nonfarm enterprises. The policy implications of these and other findings are discussed.